Reflecting on children’s literature considering translation and adaptation - Bezerra Cacho, Marília; de Oliveira Branco, Sinara (Revista Letras Raras, 2024)
Secular children’s literature which has lasted also through translation and adaptation are experienced either via oral literature or TV/books storytelling. These texts come originally from different cultural contexts and are spread by interpretations which keep the texts alive and amplify their comprehension. This paper aims at relating translation, adaptation and children’s literature, seeking to reflect on how the knowledge about translation and adaptation may be useful to consider children’s literature classic tales. Classified as a conceptual research (Williams; Chesterman, 2009), these are the main authors and their discussion areas considered as theoretical background: Jakobson (2012), Bassnett (2002), Plaza (2003) and House (2013) on translation; Katan (1999), Laraia (2001), Bassnett (2002) and Santos (2010) on culture; Hutcheon (2013) and Ribas (2014) on adaptation; and Lajolo and Zilberman (2007), Silva (2009) and Macêdo (2019) on a brief discussion about children’s literature, including the adaptation of classic tales. Coming to terms with the idea discussed, considering linguistic, aesthetic and cultural aspects, may be an enlightening resource to understand how these texts are reinterpreted in new contexts, focusing on the genre and opening space for the narratives already known by the general public to be reconstructed in new cultures in different moments of life, and valuing translation and adaptation to be considered independent from the source text from a perspective that considers new audiences and contexts.